2010
DOI: 10.1007/s10973-010-0997-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimum parameters in the high resolution thermogravimetric analysis (HRTG) for cementitious materials

Abstract: DETERMINATION OF THE OPTIMUM PARAMETERS IN THE HIGH RESOLUTION THERMOGRAVIMETRIC ANALYSIS FOR CEMENTITIOUS MATERIALS ABSTRACTIn this paper the methodology to utilization of High Resolution Thermogravimetric (HRTG) software for construction materials like Portland cement pastes is presented. The aim of this technique is to make easier the changes identification of the decomposition reactions that frequently are overlapping on conventional Thermogravimetric Analysis (TG). The optimum parameters about sample mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
(12 reference statements)
0
13
0
4
Order By: Relevance
“…Mineralogical analysis was carried out with HRTG on a Mettler-Toledo TG 850 in aluminum crucibles of 100 μL with a sealable lid perforated, in the presence of a self-generated atmosphere, and without purge gas in accordance with the optimal parameters found by Tobón et al [8], which are shown in Table 1. The conventional TG was done in a STA409 of the Netzsch, with a range between 20° and 700° C and a heating rate of 10° Cmin -1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineralogical analysis was carried out with HRTG on a Mettler-Toledo TG 850 in aluminum crucibles of 100 μL with a sealable lid perforated, in the presence of a self-generated atmosphere, and without purge gas in accordance with the optimal parameters found by Tobón et al [8], which are shown in Table 1. The conventional TG was done in a STA409 of the Netzsch, with a range between 20° and 700° C and a heating rate of 10° Cmin -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Using the modules of high-resolution in thermogravimetric analysis software (HRTG) the problem could be solved. These modules increase the resolution to reasonable testing times [1,[4][5][6][7][8] and can be applied successfully in the analysis of construction materials if the correct parameters are selected as was suggested by Tobón et al [8] With the use of HRTG, a new difficulty is found, due to the fact that the hydrated mineralogical phases of cement are not stoichiometric materials, it is common that the same phase show two or three peaks corresponding to different decomposition phenomena [8]. Because of this, a detailed study about the identification of cement-hydrated phases is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HRTG have commonly been applied in the decomposition of minerals (hydrotalcite, organoclays, peisleyite, montmorillonite), polymers and oil shales [6][7][8][9][10][11][12][13]. In the field of civil construction, only few studies have been reported using HRTG technique [14][15][16][17][18]. Payá et al [14] applied this technique in the study of dehydration of gypsum, yielding the total separation of the two decomposition processes for CaSO 4 .2H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos autores apuntan que el uso de velocidades de calentamiento reducidas y la eliminación del uso de gas portador favorecen la formación de una atmósfera autogenerada de vapor de agua que permite un aumento de la presión de vapor de este gas permitiendo que la degradación de los hidratos se lleve a cabo de manera más estable durante la calefacción de la muestra (Tobón et al, 2012a(Tobón et al, , 2012b.…”
Section: Influencia Del Uso De Gas Portadorunclassified
“…Otros autores empleando regímenes dinámicos de calentamiento (Tobón et al, 2012b) proponen una disminución de la temperatura a la cual se alcanza un determinado grado de conversión o pérdida de masa. Este razonamiento estaría relacionado con que mientras la reacción tiene lugar,…”
Section: Influencia Del Uso De Gas Portadorunclassified